The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1207/s15327019eb0902_6
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Professionals and Assisted Death: Perceived Ethical Obligations and Proposed Guidelines for Practice

Abstract: I have three purposes in this article: (a) to briefly review the legal obligations a mental health professional has when working with a client who is talking about taking some action that could lead to his or her death, (b) to clarify the positions of the 4 major national mental health organizations regarding the acceptable roles of their members with clients who are discussing the possibility of receiving assisted death, and (c) to propose a set of guidelines for practice for mental health professionals worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(57 citation statements)
references
References 0 publications
2
55
0
Order By: Relevance
“…The results indicating support for rational suicide are particularly interesting in light of the ACA (1995) ethical guidelines that promote clinical involvement, at all costs, in instances in which suicide is a possible outcome (see also Werth, 1999b). Again, these findings provide valuable insight into the beliefs and attitudes of therapists regarding rational suicide and may be useful for ACA to consider as individual states continue to grapple with the issue in the future.…”
Section: Discussionmentioning
confidence: 80%
“…The results indicating support for rational suicide are particularly interesting in light of the ACA (1995) ethical guidelines that promote clinical involvement, at all costs, in instances in which suicide is a possible outcome (see also Werth, 1999b). Again, these findings provide valuable insight into the beliefs and attitudes of therapists regarding rational suicide and may be useful for ACA to consider as individual states continue to grapple with the issue in the future.…”
Section: Discussionmentioning
confidence: 80%
“…55 These guidelines may ultimately influence national associations or organizations to develop codes of ethics in discussing rational suicide by the individual.…”
Section: 54mentioning
confidence: 99%
“…65 Further, it is suggested that not discussing these options may be disrespectful of a patient's needs and shirking professional responsibilities. 55 From a holistic existential therapy perspective, exploration of existential coherence-how one coheres to the external world-is encouraged. 68 The innermost layer of existential coherence deals with the core question of whether one wants to live or die, and it is believed that suicidal crises arise from people questioning whether they wish to accept responsibility for their lives.…”
Section: Discussing Suicidalitymentioning
confidence: 99%
“…For ACA, the only involvement on EOL issues that was identified was signing onto an amicus curiae (friend of the court) brief in 1995 for the two "assisted suicide" cases that were before the U.S. Supreme Court at the time (i.e., Vacco v. Quill, 1997;Washington v. Glucksberg, 1997) and even this was documented in published articles (Cohen, 2001;Werth, 1999a;, not on the Web site.…”
Section: Review Of the Literaturementioning
confidence: 99%